REQUIRED EVALUATION OF ARMADA AND SPECIFIED TARIFF OF TAXI IN SURAKARTA - Suwardi Suwardi (Institut Teknologi Sepuluh Nopember (ITS), 2010)
The research objectives were analyzed the number of taxis as well as the operational cost in field conditions. Analyzing the balanced of public transport following by its performance. Research benefits as an input to the Surakarta government as the policy holder and also for the entrepreneur as a control of construction with profit oriented. This study used the descriptive analytic method. The analysis result are the number of taxi with six businessmen, the total fleet was 479 fleets, after the analysis was 412 fleets, mileage taxis every day in the field was 228 km/day, after the analysis was 266 km/day. Mileage taxis fill every day in the field was 157 km/day, after analysis was 182 km/day. When operating in the field and the analysis was 22 hours/day. Travelling time in the field was 8 hours/day. After the analysis was 9 hours/day. Load factor of taxi in the field was 69%. Load factor after the analysis was 81%. Load factor of time was 37% field conditions. Load factor was 43% after analysis. Tariffs field condition was 2.769/km. after analysis was 2.410/km, while taxi fares in the field was 2.750/km.